Lipoarabinomannan as a Point-of-Care Assay for Diagnosis of Tuberculosis: How Far Are We to Use It? - Flores, Julio; Cancino, Juan Carlos; Chavez-Galan, Leslie (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is still a severe public health problem; the current diagnostic tests have limitations that delay treatment onset. Lipoarabinomannan (LAM) is a glycolipid that is a component of the cell wall of the bacillus Mycobacterium tuberculosis, the etiologic agent of TB. This glycolipid is excreted as a soluble form in urine. The World Health Organization has established that the design of new TB diagnostic methods is one of the priorities within the EndTB Strategy. LAM has been suggested as a biomarker to develop diagnostic tests based on its identification in urine, and it is one of the most prominent candidates to develop point-of-care diagnostic test because urine samples can be easily collected. Moreover, LAM can regulate the immune response in the host and can be found in the serum of TB patients, where it probably affects a wide variety of host cell populations, consequently influencing the quality of both innate and adaptive immune responses during TB infection. Here, we revised the evidence that supports that LAM could be used as a tool for the development of new point-of-care tests for TB diagnosis, and we discussed the mechanisms that could contribute to the low sensitivity of diagnostic testing.